Education and Control after Disciplinary Societies: A Reading of Deleuze's Postscript - Capodivacca, Silvia (Scenari, 2023)
In 1990 Deleuze published a short text in which he introduced the concept of control to describe the social order following what Foucault had named in the terms of the disciplinary society. In addition to predicting several developments that actually occurred in the following decades and still characterize our world today, alongside prisons and hospitals in this article Deleuze considers the example of the school, showing its transformations and related drifts. This essay proposes an analysis of Deleuzean writing, a focus on the pedagogical question and some possible solutions or, more appropriately, lines of escape to be drawn in order to arm ourselves with ‘new weapons’ against the consequences of these practices of power.